TRENDS IN THE DIAGNOSIS OF HUMAN IMMUNODEFICIENCY VIRUS - G, Santhosh Kumar; J, Manjula; C, Rajasekaran; MN, Manoj; PV, Subbarao; Nair, Chandrasekhar B (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Ever since the first HIV case reported, there is a dramatic increase in the prevalence of HIV infection which urged the need for an effective diagnostic method.Â  There are several improvements in diagnostic methods employing various technologies to screen for HIV infection using enzyme immunoassays and rapid diagnostic tests which simultaneously detect antigen and antibody with significantly reduced window period.Â  Further, western blot or immunofluorescence methods are used to confirm the results. Nucleic acid amplification tests, though sensitive, are expensive and hence not employed for screening but instead used to monitor the antiretroviral drug response. In spite of appreciable advancements in the sensitivity and specificity of the detection techniques, the algorithms are still the method of choice for ensuring the accuracy of test results.